2020
DOI: 10.3390/jcm9030835
|View full text |Cite
|
Sign up to set email alerts
|

The Effect of (Poly)phenol-Rich Interventions on Cognitive Functions and Neuroprotective Measures in Healthy Aging Adults: A Systematic Review and Meta-Analysis

Abstract: Context: As the food industry is continually involved in the development of new attractive alternative therapeutic agents, the evaluation of the beneficial impact of (poly)phenols on cognitive and brain function during aging has gained increasing interest. Objective: This systematic review and meta-analysis aimed to evaluate the acute and chronic effects of (poly)phenol-rich diet supplementation on cognitive function and brain health in aging adults. Data Sources: PubMed and Web of Science databases were searc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
57
1
2

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 30 publications
(64 citation statements)
references
References 76 publications
(241 reference statements)
2
57
1
2
Order By: Relevance
“…Concerning the neuroprotective effects, a recent systematic review (SR) and meta-analysis (MA) examining the effects of (poly)phenol-rich supplementation on age-related cognitive decline suggested polyphenol-rich supplementation may improve some cognitive and brain functions in older adults. However, it failed to provide evidence regarding the neuroprotective and anti-inflammatory effect of (poly)phenol supplementation in aging adults [20]. Findings from some individual studies, included in this SR, indicate that polyphenol consumption modulates cerebral hemodynamics [24] and resting regional cerebral blood flow [25,26], while simultaneously enhancing psychomotor functions, speed of attention, episodic memory, verbal fluency and overall cognitive performance in older-aged adults [24,27,28].…”
Section: Introductionmentioning
confidence: 92%
See 3 more Smart Citations
“…Concerning the neuroprotective effects, a recent systematic review (SR) and meta-analysis (MA) examining the effects of (poly)phenol-rich supplementation on age-related cognitive decline suggested polyphenol-rich supplementation may improve some cognitive and brain functions in older adults. However, it failed to provide evidence regarding the neuroprotective and anti-inflammatory effect of (poly)phenol supplementation in aging adults [20]. Findings from some individual studies, included in this SR, indicate that polyphenol consumption modulates cerebral hemodynamics [24] and resting regional cerebral blood flow [25,26], while simultaneously enhancing psychomotor functions, speed of attention, episodic memory, verbal fluency and overall cognitive performance in older-aged adults [24,27,28].…”
Section: Introductionmentioning
confidence: 92%
“…Other studies in similar populations have reported nonsignificant effects on certain cognitive functions, specifically executive functioning, working memory and verbal memory [29,30], or cerebral blood flow response [31]. Authors of the previous SR and MA concluded the beneficial effect of polyphenols was dependent on ingested dose and bioavailability, suggesting more promising findings may be found in younger populations [20].…”
Section: Introductionmentioning
confidence: 97%
See 2 more Smart Citations
“…Gojazne osobe se podložnije ozbiljnijim kliničkim oblicima bolesti i u većem su riziku od hospitalizacije, usled hronične inflamacije nižeg stepena [5], izmenjenog imunološkog odgovora na infekciju, kao i sledstvenih kardiometaboličkih komorbiditeta [6]. U pojedinim studijama utvrđena je značajna veza između načina ishrane, bavljenja fizičkim aktivnostima i raspoloženja [7,8,9]. U literaturi se navode brojne psihičke tegobe poput anksioznosti kod lica lišenih slobode [10].…”
Section: Ishrana Studenata I Nastavnika Visoke šKole U Subotici Tokomunclassified